BIO-LINGUISTICS ACQUISITION OF BALINESE MEDICINAL PLANTS BY BIOLOGY STUDENTS - Ida Bagus Nyoman Mantra; Dewa Ayu Puspawati; Ida Ayu Made Sri Widiastuti; Nengah Dwi Handayani (International Journal of Applied Science and Sustainable Development (IJASSD), 2020)
Plants are the closest nature of human life. People basically cannot live well without plants, therefore generally people have some knowledge about plants which are familiar with their daily life. This study was intended to analyze the bio-linguistics acquisition of Balinese medicinal plants by biology students. Medicinal plants are not something new for the community but they are included in their local wisdom. This study revealed that the benefits of medicinal properties for health have been known and used by the community widely. Furthermore, the present study also revealed that Biology students have sufficient knowledge of linguistic terminology on Balinese medicinal plants. Therefore further learning processes should be intensified to enhance their comprehension of the Balinese medicinal plants.